The determinants of R&D Investment: the role of Cash flow and Capabilities - Francesco Bogliacino; Sebastian Gómez Cardona (European Commission, Joint Research Centre (JRC), 2010)
In this paper we have estimated a behavioural equation for R&D investment. We assess the impact of liquidity constraints and capabilities, measured respectively as internal cash flow and distance from the technological frontier. Our estimation is performed on an industry level panel covering fifteen European countries from 1996 to 2005 and on a sample of European R&D performers extracted from COMPUSTAT covering 2000-2008. Both at industry level and firm level we found that financing constraints exist and that the distance from the frontier negatively affects the decision to engage in R&D. We claim that the implied divergence pattern opens a gap for policy intervention, but that these policies should be correctly tailored and should also promote enablers of technological change.
Keywords: D24; L50; O33; 330; R&D; liquidity constraints; technological frontier; panel data